Physical activity in stroke patients: A scoping review - Ariyati Amin; Rosyidah Arafat; Rini Rachmawaty (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Stroke is the second leading cause of disability and death worldwide with 5.9 million deaths annually. Stroke can be followed by various clinical problems. Impaired motoric function of the extremities is the most severe post stroke disorder experienced and impacts on limitations of daily activities. The main treatment is by doing regular physical activity exercises. This review was conducted to identify physical activities that can be performed by stroke patients. This scoping review was compiled using Arksey and O'Malley's five-stage framework. A total of three databases (i.e., Pubmed, Proquest, and DOAJ) was searched with relevant keyword